Protective role of bayberry extract: associations with gut microbiota modulation and key metabolites. Issue 10 (27th April 2022) - Tu, Pengcheng; Tang, Qiong; Wang, Meng; Chen, Wen; Ye, Xiang; Zheng, Xiaodong
Abstract : We aimed to investigate the metabolic impact of bayberry extract cyanidin-3- O -glucoside and its associations with changes in the gut microbiota. Abstract : Dysbiosis of the gut microbiota is inextricably intertwined with the onset and development of metabolic diseases. Dietary modulation of the gut microbiota has received much attention in recent years; however, currently there are still few effective approaches. Polyphenols extracted from fruits protect against metabolic disorders, and this effect is associated with the gut microbiota. We aimed to investigate the metabolic impact of bayberry extract cyanidin-3- O -glucoside and its associations with changes in the gut microbiota. Based on C57BL/6 and db/db mouse models, combined with 16S rRNA high-throughput sequencing and metabolomic profiling, we found that C3G administration reduced weight gain and fasting blood glucose levels. More importantly, C3G significantly modulated the gut microbiota including its composition, diversity and functional pathways. A distinct metabolite profile in addition to alterations of key metabolites was observed probably resulting from changes in the gut bacterial composition and metabolic pathways induced by C3G administration. This study may provide evidence for the missing link in mechanisms underlying the beneficial effects of poorly absorbed dietary polyphenols.